Prenatally diagnosed giant umbilical cord resulted from patent urachus in a monochorionic diamniotic twin with selective intrauterine growth restriction - Satoko Matsuyama; Fumi Matsumoto; Futoshi Matsui; Koji Yazawa (Urology Case Reports, 2023)
A long diffuse giant umbilical cord (GUC), caused by umbilical cord edema associated with a patent urachus, is an extremely rare anomaly. While patients with diffuse GUC appear to experience no significant complications and a good prognosis, little is known about their etiology and prenatal course. Here, we report the first case of prenatally diagnosed diffuse GUC resulted from patent urachus in a monochorionic diamniotic twin with selective intrauterine growth restriction. This case indicates that GUC is epigenetic and unrelated to multiple births.